Socio-economic development and fiscal policy: lessons from the cohesion countries for the new member states - Aaron N. Mehrotra; Tuomas A. Peltonen (European Central Bank (ECB), 2005)
This paper examines the link between socio-economic development and fiscal policy. We introduce an indicator for socio-economic development (SEDI) and investigate its relationship with different fiscal variables, using data for the cohesion countries, namely Greece, Portugal, Spain and Ireland for 1980-1999. We find that an improvement in the net lending position of the government, as well as a fall in the level of public debt, would be beneficial for socio-economic development in the medium term. Furthermore, fiscal consolidation is found to be more relevant for promoting socio-economic development in the cohesion countries than in the other EU-15 Member States. Our results provide support for incentives to curb spending, such as the fiscal criteria of the Maastricht Treaty or the Stability and Growth Pact.
Keywords: H6; H5; I0; 330; EU enlargement; fiscal consolidation; socio-economic development; Stability and Growth Pact; Soziale Lage; Sozialer Indikator; Finanzpolitik; Wirtschaftliche Konvergenz; Griechenland; Portugal; Spanien; Irland; Europäischer Stabilitätsmechanismus